1989
DOI: 10.1021/jm00122a016
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase synthesis of 16 potent (selective and nonselective) in vivo antagonists of oxytocin

Abstract: We describe the synthesis and some pharmacological properties of 16 new in vivo antagonists of oxytocin. These are based on modifications of three peptides: A, B, and C. A is our previously reported potent and selective antagonist of the vasopressor (V1 receptor) responses to arginine-vasopressin (AVP)/weak oxytocin antagonist, [1-(beta-mercapto-beta,beta-pentamethylenepropionic acid), 2-O-methyltyrosine]arginine-vasopressin (d(CH2)5[Tyr(Me)2]AVP. B reported here, the Ile3 analogue of A, is d(CH2)5[Tyr(Me)2]AV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 8 publications
1
66
1
1
Order By: Relevance
“…In the present investigation, we chose a dose approximately 10-fold higher than in the previous study, because in our experience sensitivity to infused peptides tends to be lowered during anaesthesia. The antagonist has negligible effects on vasopressin V 2 receptors (Manning et al 1989) and, although it has been reported to partially block V 1 receptors (Manning et al 1989), it had no effect on arterial pressure in the present study. (In any case, plasma vasopressin concentrations did not reach pressor levels.)…”
Section: Resultscontrasting
confidence: 59%
“…In the present investigation, we chose a dose approximately 10-fold higher than in the previous study, because in our experience sensitivity to infused peptides tends to be lowered during anaesthesia. The antagonist has negligible effects on vasopressin V 2 receptors (Manning et al 1989) and, although it has been reported to partially block V 1 receptors (Manning et al 1989), it had no effect on arterial pressure in the present study. (In any case, plasma vasopressin concentrations did not reach pressor levels.)…”
Section: Resultscontrasting
confidence: 59%
“…Therefore, we used a selective oxytocin antagonist and an agonist to determine if oxytocin receptors participate in the luminal action of AVP. When 10-6 M GN-OVT, a selective oxytocin antagonist (15), was in the lumen together with AVP, the effect of luminal AVP was inhibited (Fig. 8).…”
Section: Resultsmentioning
confidence: 97%
“…In females, continuous infusion of OXT into the lateral ventricle via osmotic minipumps reduces anxiety in lactating rats [74] as well as in virgin female rats nonselected for anxiety [86]. Furthermore, the same treatment/ application method leads to decreased anxiety in virgin HAB rats, whereas chronic administration of a selective OXT-R antagonist (OXT-A) [87] results in increased anxiety in virgin LAB rats [88]. Regarding MA in HAB mothers, a high amount of OXT is released especially in the PVN and the central amygdala (CeA) during the display of MA (for details see below) [3].…”
Section: (I) the Mother's Innate Anxiety Affects Maternal Aggressionmentioning
confidence: 99%